Family home food environment and nutrition-related parent and child personal and behavioral outcomes of the HOME Plus study: A randomized controlled trial - Fulkerson, Jayne A. (J Acad Nutr Diet, 2017)
BACKGROUND: Research has demonstrated a significant positive association between frequent family meals and children’s dietary intake; however, the promotion of healthful family meals has not been rigorously tested for key food environment and nutrition-related behavioral outcomes in a randomized trial. OBJECTIVE: To describe family home food environment and nutrition-related parent and child personal and behavioral outcomes of HOME Plus, the first rigorously-tested family meals intervention targeting childhood obesity prevention. DESIGN: Randomized controlled trial. Baseline, post-intervention (12 months, 93% retention) and follow-up (21 months, 89% retention) data (surveys, dietary recalls) were collected. PARTICIPANTS/SETTING: 8–12 year-old children (n=160) and their parents were randomized to intervention (n=81) or control (n=79) groups. INTERVENTION: The intervention included five parent goal-setting calls and 10 monthly sessions delivered to families in community settings that focused on experiential nutrition activities and education, meal planning, cooking skill development and reducing screen time. MAIN OUTCOME MEASURES: Family home food environmental outcomes and nutrition-related child and parent personal and behavioral outcomes. STATISTICAL ANALYSES PERFORMED: Analyses used generalized linear mixed models. Primary comparisons were contrasts between intervention and control groups at post-intervention and follow-up, with adjustments for child age and parent education. RESULTS: Compared to control parents, intervention parents showed greater improvement over time in scores of self-efficacy for identifying appropriate portion sizes, with significant differences in adjusted means at both post-intervention (p=0.002) and follow-up (p=0.01). Intervention children were less likely to consume at least one sugar-sweetened beverage daily at post-intervention than control children (p=0.04). CONCLUSIONS: The HOME Plus program involved the entire family and targeted personal, behavioral, and environmental factors important for healthful changes in the home food environment and children’s dietary intake. The intervention improved two nutrition-related behaviors and this may inform the design of future family meal interventions.